PENERAPAN PIDANA OLEH HAKIM TERHADAP PELAKU TINDAK PIDANA PEMBAKARAN HUTAN (ANALISIS PUTUSAN NOMOR : 159/PID.B/LH/2018/PN.MRB DAN PUTUSAN NOMOR : 201/PID.B/LH/2017/PN.MRB) - Zulfanur Fitri (UNES Law Review, 2020)
Forests are an invaluable asset of the nation and state. The state based on its authority has made several legal products to protect forests from human actions. As happened in the jurisdiction of the Muaro Bungo District Court who has imposed a criminal offense against the perpetrators of forest fires in the ruling No.159 / Pid.B / LH / 2018 / PN.Mrb. and Decision No.201 / Pid.B / LH / 2017 / PN.Mrb. The problems to be studied are how the application of criminal sanctions, and Judges considerations in issuing criminal decisions against perpetrators of forest fires. The approach used is a normative approach. The data used are secondary data. The data used is only secondary data. The technique of data collection is through library research and document study in the form of Judge's Decree No.159 / Pid.B / LH / 2018 /PN.Mrb and Judge's Decree No. 201 / Pid.B / LH / 2017 / PN.Mrb. The data is then analyzed normatively and presented in a descriptive qualitative form. The results of the study showed that: First, the application of punishment by the judge in the decision No.159 / Pid.B / LH / 2018 / PN.Mrb. and Decision No.201 / Pid.B / LH / 2017 / PN.Mrb. that Article 56 Paragraph (1) in conjunction with Article 108 of Law Number 39 Year 2014 concerning Plantation in conjunction with Article 55 paragraph (1) 1st of the Criminal Code. Second, the judge's consideration in making a decision No.159 / Pid.B / LH / 2018 / PN.Mrb. and Decision No.201 / Pid.B / LH / 2017 / PN.Mrb. are: considerations of a juridical nature indictment, witness testimony, defendant's letter, evidence, non-juridical considerations: the defendant's physical and spiritual condition, as a result of the defendant's actions.